A Study on Curing Temperature and Fracture Mechanism of Carbon and Glass Fiber Reinforced Polymers Using an Electron Microscopy - Man, Tial Cuai; Karin, Preechar; Lin, Ye Htet; Larpsuriyakul, Patcharee; Ohtake, Naoto (My University, 2021)
The morphology and nanostructure of carbon and glass fiber are investigated by using XRD, SEM and TEM analysis. The composites are divided into three groups which consists of “without post-curing”, “post-cured at 80 °C for 6 hrs” and “post-cured at 120 °C for 3 hrs” to investigate curing temperature effect. The mechanical properties of composites are tested in the indentation, tensile, and flexural machine with ASTM standard. According to the results, the hardness of post-curing of carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP) are increased approximately three-times and 5 % compared to with and without post-curing process. The tensile strength of CFRP and GFRP are approximately 458 MPa and 385 MPa, while post-cured at 120 °C for the three-hour results are 490 MPa and 433 MPa respectively. In contrast, composites of treated fiber are not improved mechanical strength significantly for CFRP, while GFRP are slightly increased by 7 %. On the other hand, the flexural strength of treated carbon and glass fiber of composite are increased to 3 % and 15 % respectively. Higher temperature and treated fiber composites of carbon fiber are not significantly improved because high temperature curing and treated fiber created more porous to occur fracture internally.
Keywords: Carbon fiber; Composite material; Electron microscopy; Fracture mechanism; Glass fiber; Nanostructure